2011
DOI: 10.1021/bm2008795
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Films Based on Xylan-Rich Hemicelluloses and Cellulose Nanofibers with Enhanced Mechanical Properties

Abstract: Interest in xylan-rich hemicelluloses (XH) film is growing, and efforts have been made to prepare XH films with improved mechanical properties. This work described an effective approach to produce nanocomposite films with enhanced mechanical properties by incorporation of cellulose nanofibers (CNFs) into XH. Aqueous dispersions of XH (64-75 wt %), sorbitol (16-25 wt %), and CNF (0-20 wt %) were cast at a temperature of 23 °C and 50% relative humidity. The surface morphology of the films was revealed by scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(98 citation statements)
references
References 64 publications
7
90
1
Order By: Relevance
“…Several studies have shown that plasticizers can be used at controlled levels to adjust the degree of compliance or rigidity of films that contain nanocellulose reinforcements (Angles and Dufresne 2000;Dufresne et al 2000;López-Rubio et al 2007;Svagan et al 2007;Azeredo et al 2010;Mikkonen et al 2011;Peng et al 2011;Hansen et al 2012;Trovatti et al 2012ab;Barud et al 2013;Fortunati et al 2014;Pereda et al 2014;Alves et al 2015).…”
Section: Use Of Plasticizer Vs Mechanical Poperiesmentioning
confidence: 99%
“…Several studies have shown that plasticizers can be used at controlled levels to adjust the degree of compliance or rigidity of films that contain nanocellulose reinforcements (Angles and Dufresne 2000;Dufresne et al 2000;López-Rubio et al 2007;Svagan et al 2007;Azeredo et al 2010;Mikkonen et al 2011;Peng et al 2011;Hansen et al 2012;Trovatti et al 2012ab;Barud et al 2013;Fortunati et al 2014;Pereda et al 2014;Alves et al 2015).…”
Section: Use Of Plasticizer Vs Mechanical Poperiesmentioning
confidence: 99%
“…HL powder was amorphous, showing a broad scattering centered at 2θ = 20°. 7/3 HL/S film exhibited a peak at 2θ = 18°and a small shoulder at 2θ = 21°( Figure 5), indicative of its partially crystalline structure, likely from the crystallinzation of xylan-rich hemicelluloses of rice straw as neither amorphous lignin nor sorbitol less than 50% 35,48 could impose crystalline structural change. Depending on the extraction methods and sources, rice straw hemicelluloses have shown to consist of 32−60% xylan, 8−43% glucan and a small amount of arabinan and galactan.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…In this approach, hemicelluloses represent many promising properties for the manufacture of value-added polymeric composites and blends, which could replace materials currently manufactured from fossil resources or even metals, such as aluminum (Alekhina et al 2014). Natural biopolymers are considered to have many advantageous properties when compared to their synthetic counterparts, as they are abundant, low-cost, biocompatible, nontoxic, biodegradable, and environmentally safe (Peng et al 2011b;Šimkovic et al 2011). Of the several possible hemicelluloses-derived polymeric applications, the manufacture of various polymeric films and hydrogels has garnered the most interest.…”
Section: Polysaccharide-based Biodegradable Films and Hydrogelsmentioning
confidence: 99%